Intravitreal Bevacizumab with or without Triamcinolone for Refractory Diabetic Macular Edema: Long-term Results of a Clinical Trial - Shoeibi, Nasser (Ophthalmic Research Center, 2013)
PURPOSE: To report the long-term results of intravitreal bevacizumab (IVB) injection alone or combined, at the time of first IVB injection, with intravitreal triamcinolone acetonide (IVT) for treatment of refractory diabetic macular edema (DME). METHODS: In this randomized clinical trial, 115 eyes of 101 patients with refractory DME were enrolled and randomly assigned to one of the three study arms: the IVB group (41 eyes) received three consecutive injections of 1.25 mg IVB at 6-week intervals; the IVB/IVT group (37 eyes) additionally received 2 mg of IVT at the time of first IVB injection; and the control (sham injection) group. Patients in the IVB and IVB/IVT groups were followed for a mean of 13.3 months and received retreatment with IVB alone whenever indicated. Main outcome measures were best corrected visual acuity (BCVA) and central macular thickness (CMT). RESULTS: At the last follow up, CMT decreased significantly in the IVB group (p=0.013) but it was not significant (p=0.13) in the IVB/IVT group. Mean CMT improvement was 91 (95% CI, 20 to 161) microns and 57 (95% CI, -18 to 133) microns in the IVB and IVB/IVT groups, respectively. Mean BCVA improvement from baseline was 0.28 (95% CI, 0.18 to 0.38) logMAR (P=0.017) in the IVB group and 0.19 (95% CI, 0.08 to 0.30) logMAR (P=0.001) in the IVB/IVT group. There was no difference between the two groups in terms of visual improvment (p=0.42). In generalized linear mixed model, only the time interval between the last injection and CMT measurement was statistically significant (P=0.04). The same results were repeated for visual acuity (P=0.03). CONCLUSION: Three loading doses of IVB (added doses if required) have long-term beneficial effects for treatment of refractory DME. Adding triamcinolone to this regimen provides no additional long-term benefit.